Real-time FPGA based human iris recognition system - Amirshahram Hematian, 1984-; Suriayati Chuprat; Sekolah Informatiks Termaju (2013)
Thesis (Sarjana Sains (Kejuruteraan Perisian)) - Universiti Teknologi Malaysia, 2013